Assessment of the impact of different N terminal pro brain natriuretic peptide thresholds on echocardiography services. (8th December 2021) - Yii, Eric; Fersia, Omar; McFadyen, Angus; Isles, Christopher
Abstract: Aims: N terminal pro brain natriuretic peptide (NT‐proBNP) is considered a rule‐out test for patients with suspected heart failure. The NT‐proBNP thresholds recommended for echocardiography by the European Society of Cardiology (ESC) and National Institute for Health and Care Excellence (NICE) are based on small studies of patients with heart failure and left ventricular (LV) systolic dysfunction (LVSD). The purpose of our study was to examine the relation between NT‐proBNP and LVSD in a larger number of patients with symptoms suggestive of heart failure in a non‐acute setting. Methods and results: One thousand patients with suspected chronic heart failure underwent echocardiography within 6 months of NT‐proBNP measurement. NT‐proBNP was the strongest predictor of any form of LVSD in univariate (OR 2.52, 95% CI 2.19–2.91, P value < 0.001) and multivariate (OR 2.73, 95% CI 2.32–3.21, P value < 0.001) analyses. Negative predictive value (NPV) of NT‐proBNP for impaired LV systolic function (ejection fraction 35–49%) was 98% at 125 pg/mL (the ESC threshold), 93% at 400 pg/mL (the NICE threshold), 91% at 1000 pg/mL and 90% at 2000 pg/mL. Corresponding values for severe LVSD (ejection fraction <35%) were 100%, 99%, 98% and 96%. The number of patients per 1000 with suspected chronic heart failure requiring echocardiography at each threshold was 851, 543, 324, and 182, respectively. Conclusions: N terminal pro brain natriuretic peptide thresholds recommended by ESC and NICE result in large numbers of patients with suspected chronic heart failure being referred for echocardiography. Raising the NT‐proBNP threshold would improve access to echocardiography with minimal negative impact on the clinical performance of this cardiac biomarker.